Tuberculosis and Stigma in India: Evidence from a Nationally Representive Survey (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2020)
Introduction: Infectious nature of pulmonary tuberculosis (TB) is one of the major reasons behind the prevailing stigma and negative attitude towards the disease. These factors stand in the way of seeking an early diagnosis or continuing treatment following a positive diagnosis. This study aims at exploring the shares of adult men and women conforming to TB related stigma in India, a high TB burden nation, and the causal factors behind the same.Methodology: The study uses unit level data on adult men and women from the nationally representative survey NFHS-3 (2005-06). Simple tools for descriptive statistics and logistic regression analysis have been employed.Results: Factors affecting TB related stigma among Indian men are age, religion, economic class ,education level, family structure and marital status. In case of women age plays no role. However, place of residence, social group and employment status emerge as significant factors impacting stigma among Indian women. Further, stigma levels vary across Indian states for both genders.Conclusion: Socio-economic and demographic factors that have a role to play in shaping people’s attitude towards disease and related health seeing behaviour need to be acknowledged and incorporated in policies targeted towards elimination of TB.